Islamic Economic Ethics and Social Capital in Waste Bank Empowerment: A Study of BUMDes in Blitar - Nur Isnaini, Ulya; Nurohman, Dede; Huda, Qomarul; Fuad, Ah Zaki (Sekolah Tinggi Ekonomi Syariah Manna Wa Salwa, 2025)
This study explores how Village-Owned Enterprises (BUMDes) operate in two locations: BUMDes Karya Bakti in Pojok Village and BUMDes Suraya in Banggle Village. The central issue lies in the fact that while many BUMDes experience declining performance, some remain resilient. One BUMDes, in particular, continues to perform stably, which is presumed to be due to the strength of its social capital. Therefore, this research is significant in examining how social capital is applied within these two BUMDes and understanding the reasons behind their differing performance levels. This study employs a qualitative research approach using case studies and the maqāṣid al-sharī‘ah framework. The findings reveal that trust, norms, and social networks play a central role in fostering participation, collaboration, and sustainability. In Banggle, collective leadership and participatory governance have enabled the integration of social capital into well-structured institutional system, reflecting ecological citizenship and ukhuwwah (social solidarity) as the foundation of empowerment. Meanwhile, in Pojok, social capital remains concentrated within a limited managerial core, resulting in lower inclusivity and greater dependence on hierarchical authority.